"Child Constitution" and its Role in Bosnia and Herzegovina - Mitrović, Ljubinko; Tomašević, Sonja (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Due to the fact that children as human beings have a special position in society, it is necessary for the community to undertake all measures and activities in order to provide special care for children and their protection. They are a special category of citizens in every country, and both national and international law recognise them as vulnerable and specific, requiring protection for which regular mechanisms of protection do not suffice. There are many different subjects of protection involved in a child’s development – parents, education institutions, centres/social care services, health institutions, judiciary, media, etc., as it foresees the human rights law. The child is, compared to the adults, becoming being regarded and treated as particularly vulnerable human being (with all their characteristics and personal autonomy and our obligation to respect and guaranty it through the norms and through the creation of the environment in which the rights of the child are recognized and implemented) in the beginning of XVII century when the awareness of the notions of the childhood and the child and their rights had been risen. The rights of the child today are a fact, that is, a reality recognised by international law. They are more or less governed by norms, and the process of regulating these rights is running and progressing at a different pace in different countries, depending on the course of social life development of that country. The notion of the rights of the child means all those rights that are inherently human and that every child has to enjoy regardless of the country he or she lives in, or in what political, cultural or economic environment he or she grows up, and in accordance with what traditions, customs and beliefs he or she develops. It is a corpus of law that originated primarily from two basic ideas, namely: 1) the children are autonomous persons with their own specific needs and rights and, consequently, they are the holders of legal claims, i.e. active legal subjects, not exclusively objects of protection by adults, and 2) due to specific psycho-physical characteristics, depending on age and level of mental maturity, children are also a particularly sensitive and vulnerable category that deserves special or additional protection of the state, i.e. all its institutions (all subjects in child protection area have an obligation and responsibility to react in a timely and appropriate manner, in accordance with their role in the best interests of the child). On the other hand, continuous cooperation, information exchange, and monitoring of the child from early development through adulthood are necessary. Only by joint actions, interventions and reactions of all subjects of protection is it possible to provide full protection of the child and to recognise situations, which could be obstacles to healthy development. The most important and influential document in the field of the rights of the child internationally is the 1989 United Nations Convention on the Rights of the Child (hereinafter: the UN Convention), which has been ratified by more than 200 countries so far. The UN Convention contains a catalogue of the rights of the child. The rights of the child enshrined in the UN Convention are interconnected and are being realized in the light of the realization of the four basic principles of the UN Convention, namely: 1) the child’s right to life, survival and development, 2) best interest of the child, 3) the right of the child to participate and 4) to right of the child to non-discrimination (Simović et al., 2013, pp. 47–63). At what stage is Bosnia and Herzegovina nowadays in terms of exercising the rights of the child, i.e. the implementation of the UN Convention, and are the children in Bosnia and Herzegovina now at a higher level of social, moral and psychological development? Has the BH society provided all the necessary conditions for healthy growing up, upbringing and education of children? Has society done enough, and could we have done more? How many children's rights are being violated in Bosnia and Herzegovina today? Many questions, and we will try to answer some of them in this paper.